2011
DOI: 10.1097/ftd.0b013e3182197e38
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Mycophenolic Acid Predose Concentrations in the Maintenance Phase More Than One Year After Renal Transplantation

Abstract: To keep the MPA AUC0-12>30 μg·h/mL, the plasma threshold for maintaining the MPA C0 with tacrolimus should be set >2.0 μg/mL as determined by high-performance liquid chromatography. For patients who are stable for >1 year after transplantation, continued monitoring of the MPA C0 using the same samples used to monitor the tacrolimus C0 and the additional assessment of the MPA AUC0-12 at the 1-year time point seem to be a viable option. If a change of the mycophenolate mofetil dose seems necessary based on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The association between the trough level of MPA and clinical outcome such as graft rejection is still controversial. Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the trough level of MPA and clinical outcome such as graft rejection is still controversial. Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the association between MPA trough level and clinical outcome such as graft rejection is still controversial. Indeed, in kidney transplantation, some retrospective studies have suggested that MPA C 0 levels may be correlated to the clinical efficiency . However, patients in almost all these studies received a therapy including CsA but very rarely Tac.…”
Section: Discussionmentioning
confidence: 99%
“…Although MPA‐AUC full‐time analysis from 0 to 12 hours (AUC 0–12hours ) is considered the gold standard for assessment of overall drug exposure, it requires at least 8–10 plasma samples drawn over a 12‐hour time interval, thus making it costly and rather impractical for everyday clinical application. In addition, a predose concentration (C 0 ) or a trough concentration, often used as a substitute indicator of AUC in TDM, was shown to be weakly correlated to MPA‐AUC 0–12hours . Therefore, the estimation of MPA‐AUC 0–12hours by using a limited sampling strategy (LSS) using a limited number of blood samples has been suggested as a sufficiently precise but still practical method for the prediction of MPA exposure in adult kidney transplant recipients …”
mentioning
confidence: 99%
“…For therapeutic monitoring of tacrolimus, the tacrolimus trough level was monitored and the dosage was adjusted to maintain a target concentration of 8 to 10 ng/mL during 1 month post-KT, 5 to 8 ng/mL during 1 month to 1 year, and 3 to 7 ng/mL afterward. Patients received either MMF or EC-MPS, and dosages were adjusted to maintain a target MPA trough concentration of 1.5 to 2.5 mg/L during 1 year post-KT [ 13 , 15 ]. Target concentration was lowered after 1 year post-KT to maintain above 1.0 mg/L.…”
Section: Methodsmentioning
confidence: 99%